Atomistic and Molecular Effects on the Surface Morphology and Film Conformation of Perfluoropolyether Lubricant Layer - Chung, Pil Seung; Park, Sejoon; Vemuri, Sesha Hari; Jhon, Myung S. (IEEE-INST ELECTRICAL ELECTRONICS ENGINEERS INC, 2015)
In this paper, we analyzed atomistic and molecular architectural effects on the film microstructure and morphological properties for the monolayer perfluoropolyether (PFPE) lubricant film by investigating PFPEs with different molecular structures and functionalities (Zdol, Ztetraol, Ztetraol multidentate, and TA-30) via large-scale coarse-grained bead-spring molecular dynamics originating from the atomistic theory. Film surface morphology was examined by average height and root mean square roughness, and the internal clusters of functional groups on the surface were characterized by the radial distribution function of functional groups, followed by the quantitative estimation of adhesion ratio and coordination number. We also illustrate the effects of molecular structure on the film conformation, which is useful to molecular design criteria for the head-disk interface.
Keywords: SIMULATION